MTBITC-induced apoptosis and cell cycle arrest of human hepatoma (HepG2) cells : a link between p53 and human telomerase? - Lamy, Evelyn; Justus Liebig University Giessen (My University, 2007)
Experimental data provide strong evidence for the effective inhibition of tumorigenesis by isothiocyanates (ITCs), enzymatic cleavage products of glucosinolates in Brassica vegetables like e.g. cabbage, broccoli or brussel sprouts. A number of ITCs have been identified as strong inhibitors of cell proliferation and apoptosis inducing agents which presents the chance for therapeutic impact of ITC-treatment on malignant transformed cells. Although much is known about ITC-induced apoptosis, many questions remain to be answered. The present study aimed to investigate the chemopreventive properties of 4-methlythiobutylisothiocyanate (MTBITC), which are still largely unknown despite its substantial quantitative presence in food plants. Thereby, this study focused on the hypothesis that p53-dependent induction of apoptosis leads to suppression of telomerase. Human telomerase is stably expressed in the majority of cancer cells but absent in normal tissues which outlines the importance of this enzyme and its compounds in the process of carcinogenesis and provides a promising target for a selective therapeutic approach of malignancies. Proof of a connection between telomerase regulation and the induction of apoptosis by ITCs would present an important detail for a better understanding of the chemotherapeutic properties of these compounds. As a result, this study showed for the first time the suppression of the telomerase catalytic subunit hTERT and the holenzyme activity in malignant transformed cells mediated by an ITC. This was accompanied by a G2/M phase arrest of the cell cycle and apoptosis induction observed by internucleosomal DNA fragmentation, flow cytometry analysis and the detection of single stranded apoptotic DNA. A collapse of the mitochondrial membrane potential, as analysed by flow cytometry with the probe JC-1 and the suppression of the anti-apoptotic multi-domain Bcl-2 protein BclxL, were preceeded by glutathione depletion. Thereby, DNA strand breakage, induced by MTBITC-treatment probably presented the initial step in the growth suppression machinery. This DNA damage was followed by an increase in the protein level of the tumor suppressor p53 and subsequent by the initialization of p21WAF1 protein expression. But also, the activation of p63 expression by MTBITC-treatment could be shown for the first time. As a conclusion, the present findings support the idea of an existing extra-telomeric, cell cycle regulation function of telomerase in HepG2 cells. The results of this study also showed that irrespective of the intense degradation kinetics of MTBITC, the strong cytostatic effect of the ITC was not markedly affected by it and suggests that although ITCs are only present at maximum concentrations in a living system for a rather short time, this might be sufficient to exert their therapeutic effects.

Die Inhibition der Tumorigenese durch Isothiocyanate (ITC), enzymatische Abbauprodukte von Glucosinolaten in Brassica-Gemüsen wie z. B. Kohl, Brokkoli oder Rosenkohl, ist durch experimentelle Daten belegt. Eine Reihe an ITC wurde als Wachstumsinhibitoren und Apoptose-induzierende Stoffe identifiziert, was die Möglichkeit eines Therapieansatzes bei maligne-transformierten Zellen durch ITC birgt. Obwohl bereits einiges über ITC-vermittelte Apoptose bekannt ist, bleiben noch viele Fragen offen. Die vorliegende Studie zielte darauf ab, die chemopräventiven Eigenschaften von 4-Methylthiobutyl isothiocyanat (MTBITC) zu untersuchen, welche noch größtenteils unbekannt sind, trotz der beachtlichen Quantität von MTBITC in Lebensmittelpflanzen. Dabei fokussierte diese Studie auf die Hypothese, dass p53-vermittelte Apoptoseinduktion eine Inhibition der Telomerase zur Folge hat. Humane Telomerase wird in den meisten Krebszellen stabil exprimiert, ist aber in normalen Geweben nicht detektierbar, was die Bedeutung dieses Enzyms und seiner Komponenten in der Karzinogenese hervorhebt und ein vielversprechendes Ziel für einen selektiven therapeutischen Ansatz bei malignen Tumoren darstellt. Der Beweis einer Verbindung zwischen Telomeraseregulation und der Apoptoseinduktion durch ITC würde ein wichtiges Detail für ein besseres Verständnis der chemotherapeutischen Eigenschaften dieser Stoffe darstellen. Als Ergebnis der hier vorliegen Studie konnte zum ersten Mal die Unterdrückung der katalytischen Untereinheit der Telomerase hTERT und der enzymatischen Aktivität durch ITC-Behandlung in malignen Zellen gezeigt werden. Dieser Effekt wurde begleitet von einem Zellzyklusarrest in der G2/M-Phase und Apoptoseinduktion, nachgewiesen durch internukleosomale DNA-Fragmentierung, durchflusszytometrische Analyse und der Detektion von apoptotischer Einzelstrang-DNA. Dem Zusammenbruch des mitochondrialen Membranpotenzials, durchflusszytometrisch analysiert mittels JC-1, und der Unterdrückung des anti-apoptotischen multi-Domänen Bcl-2-Proteins BclXL ging eine Absenkung des Glutathionspiegels voran. Dabei stellen die durch MTBITC verursachten DNA-Strangbrüche vermutlich den initialen Schritt in der Proliferationsinhibition dar. Diese DNA-Schäden waren von einem Anstieg des Tumorsuppressor p53-Proteins begleitet und im Folgenden von der Initialisierung der p21WAF1-Expression. Zum ersten Mal konnte hier auch die Aktivierung der Expression des p63-Proteins durch MTBITC-Behandlung gezeigt werden. Schlussfolgernd unterstützen die vorliegenden Ergebnisse das Konzept einer existierenden extra-telomeren, Zellzyklus-regulierenden Funktion der Telomerase in HepG2-Zellen. Die Ergebnisse dieser Untersuchung zeigen auch, dass ungeachtet der rapiden Degradation von MTBITC im untersuchen in vitro-Modell, die starken zytostatischen Effekte des ITCs auf die Zellkultur nicht merklich betroffen waren. Dies deutet darauf hin, dass obwohl nachgewiesener Weise ITC nur für relativ kurze Zeit Maximalkonzentrationen in vivo erreichen, dies dennoch ausreichend sein kann, um einen therapeutischen Effekt auszuüben.
MTBITC induzierte Apoptose und Zellzyklusarrest in humanen (HepG2) Hepatomzellen : ein Link zwischen p53 und Telomerase?
Keywords: HepG2; Isothiocyanate; MTBITC; Telomerase; Apoptose; HepG2; isothiocyanate; MTBITC; telomerase; apoptosis; ddc:610